(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Implementation of National Health Insurance (JKN) in several regions in Indonesia experiences differences in terms of expected outcomes. The recruitment of participants in business entities, especially the micro, small and medium segments, has also not been reported yet. The general objective of this research is to know the context and input in the implementation of national health insurance in Ternate City. The research method used is qualitative research. The informants in this study were the head of the Indonesian national health care insurance, the Head of the Health Service, the Head of Planning and Data, the Head of Health Financing, the Head of the Health Center, the Head of the Unit, the Director of the Dharma Ibu Hospital. Health insurance program policies in Ternate City are based on regulations issued by the Indonesian national health care insurance and Ternate Mayor Regulations. Inputs Health resources available at the health center and hospitals are mostly eligible, although there are still officers working health are not following their educational background. Payment of claims at the hospital is still experiencing delays while payments for capitation has proceeded according to the rules. Infrastructure facilities available at the health center and hospitals have fulfilled.